Uporaba bioloških zdravil v Univerzitetnem kliničnem centru Maribor - Bavec, Andrej (Zdravniški vestnik, 2008)
Background. Individual biological agents, despite their specific activity on targets, cover very broad spectrum of possibilities for use in treatment of different diseases. Their clinical use is limited to exact indications with criteria of use. Biological agents are most frequently indicated and used for the treatment of diseases, which were unsuccessfully treated with standard therapy. Methods. Use of biological agents in clinical practice at Department of rheumatology, Department of hematology, Department of gastroenterology at Clinic of internal medicine, Department of skin and venereal diseases and Department of gynecologic and breast oncology at Clinic of gynecology and perinatology was analyzed. Results. Biological agents were used for the treatment of 195 patients. All currently registered biological agents were used except anakinra, abatacept and bevacizumab. Most (86) patients were treated with infliximab, etanercept and adalimumab at the Department of rheumatology, the most frequently because of rheumatoid arthritis and ankylosing spondylitis. 69 patients were treated with trastuzumab because of breast cancer. 14 patients were treated with rituximab, ibritumomab tiukseatan, alemtuzumab and bortezomib at the Department of hematology because of non-Hodgkin lymphoma, B-cell chronic lymphocytic leukemia and multiple myeloma. 13 patients with Crohn's disease or ulcerative colitis were treated with infliximab. 11 patients were treated with efalizumab and 2 with infliximab because of psoriasis. Conclusions. Expansion of therapeutic indications is expected with more frequent use of biological agents in patients with different associated diseases. Use of biological agents earlier in the course of disease and development of new biologics, with effect on new targets in pathogenesis of diseases, can be expected on the basis of new researches.
Keywords: Arthritis, Rheumatoid; Biological Therapy; biološka zdravila; Biološko zdravljenje; bolezni; Breast Neoplasms; disease; Dojka, novotvorbe; Inflammatory Bowel Diseases; Lymphoma, Non-Hodgkin; Multiple Myeloma; Multipli mielom; Ne-Hodgkinov limfom; Psoriasis; Psoriaza; Revmatoidni artritis; therapy; uporaba; Vnetne črevesne bolezni; zdravljenje